Listeria monocytogenes meningitis in an immunocompetent 18-year-old patient as a possible diagnostic and therapeutical problem - Vrbić, Miodrag Živojin; Dinić, Marina; Jovanović, Maja; Ranković, Aleksandar; Popović - Dragonjić, Lidija; Đorđević - Spasić, Marina (Vojnosanitetski pregled, 2017)
Introduction. Listeria monocytogenes is the third most frequent cause of bacterial meningitis in adults. It commonly affects persons with defective cell-mediated immunity or advanced age, and only a few patiens with no underlying predisposition have been reported. Case report. We presented an previously healthy, 18-year-old man with typical clinical features of meningitis. On the account of earlier treatment with ceftriaxone and cerebrospinal fluid finding, an assumption of partially treated bacterial meningitis was made. The initial treatment with vancomycin and ceftriaxone, substituted on day 4 with meropenem, did not produce any clinical effect. On day 6 Listeria monocytogenes was isolated and, even as late as that, the administration of ampicillin was followed by complete recovery of the patient. Conclusion. In younger, immunocompetent individuals, in spite of the existent diagnostic and therapeutic problems, the subacute course of Listeria monocytogenes meningitis provides enough time for appropriate treatment and favorable disease outcome.
Keywords: meningitis; listeria monocytogenes; diagnosis; therapeutics; anti-bacterial agents